Aspiration of equine oocytes from immature follicles after treatment with equine pituitary extract (EPE) alone or in combination with hCG - Blanco, I. D. P. [UNESP]; Devito, L. G. [UNESP]; Ferreira, H. N. [UNESP]; Araujo, G. H. M. [UNESP]; Fernandes, C. B. [UNESP]; Alvarenga, Marco Antonio [UNESP]; Landim-Alvarenga, Fernanda da Cruz [UNESP] (Elsevier B.V., 2009)
This study examined the effect of treating mares with equine pituitary extract (EPE) alone or in combination with hCG on the recovery rate of immature follicles by transvaginal follicular aspiration (ovum pick-up; OPU). Ten normally cycling crossbred mares aged 3-15 years and weighing 350-400 kg were subjected to each of three treatments in a random sequence with each exposure to a new treatment separated by a rest cycle during which a spontaneous ovulation occurred. The treatments were (1) superovulated with 25 mg EPE and treated with 2500 IU hCG, (2) superovulation with 25 mg EPE, and (3) control (no exogenous treatment). Treatments 7 days after spontaneous ovulation; and all the follicles > 10 mm were aspirated 24 h after the largest follicle achieved a diameter of 27-30 mm for control group, and most follicles reached 22-27 mm for the EPE alone treatment. To the group EPE+hCG, when the follicles reached 22-27 mm, hCG was administered, 24 h before OPU. Superovulation increased the number of follicles available for aspiration. The total number of follicles available for aspiration was 61 in the EPE/hCG group. 63 in the EPE group and 42 in the control. The proportion of follicles aspirated varied from 63.5% to 73.8%. Oocyte recovery rate ranged from 15.0% to 16.7% and the proportion of mares that yielded at least one oocyte was 70% (7/10) in the EPE/hCG, 60% (6/10) in the EPE alone and 50% (5/10) in control group. The EPE/hCG treatment had a higher proportion of follicles with expanded granulose cells (64.4%) than the control (3.3%: p < 0.05) and the EPE treatment (25.0%). The intervals from spontaneous ovulation to aspiration were similar for all treatments (11-12 days). However, superovulatory treatment significantly increased the aspiration to ovulation interval from 15 +/- 4 days for control to 27 +/- 15 days for EPE (p < 0.05) and to 23 +/- 13 days for EPE/hCG treatment with commensurate increases in the time between spontaneous ovulations. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: OPU; Equine; Oocytes; Superovulation; EPE; hCG